Supply Chain Coordination and Decision-Making under Revenue Sharing and Cost-Revenue Sharing Contracts with Returns - Milena Bieniek; Tomasz Szapiro (Operations Research and Decisions, 2024)
The increasing prevalence of product returns poses challenges for businesses, the environment, and society. Efficient returns systems need to be developed. This article addresses the issue by presenting a game-theoretical modeling approach to optimize pricing and ordering decisions in supply chain contracts between manufacturers and retailers. Revenue-sharing and cost-revenue-sharing contracts are investigated in conjunction with two returns-handling strategies: one performed by the manufacturer and the other by the retailer. As a result, four distinct contract scenarios are derived. In each scenario, the manufacturer-leader and the retailer-follower engage in a Stackelberg game. Optimal solutions are obtained for the models. In addition, it has been shown that the supply chain can be coordinated if the manufacturer shares the revenue and returns handling costs with the retailer. Numerical analyses are conducted to illustrate the theoretical results. (original abstract)